Development of Conventional Tablets from Herbal Extracts of Jati Belanda, Kumis Kucing, Meniran, Sirih, and Turmeric for Body Weight Reduction - Tampubolon, Stephanie Angelica Rinjani; Suwitono, Marvel Reuben; Sulastri, Titin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Health problems that occur today are diverse and varied, one of which is being overweight. This study focuses on the formulation of herbal extracts in conventional tablet preparations using Jati Belanda, Kumis Kucing, Meniran, Sirih, and Kunyit which have the potential as weight loss agents. Extraction is carried out using the maceration method, then the extract is made into conventional tablets with additional ingredients: magnesium stearate, talc, PVP, Avicel pH 102, and aerosil. Evaluation of physical properties such as uniformity of size, uniformity of weight, hardness, and disintegration time has been carried out. The results of the study showed that conventional tablet preparations from various spices with 3 different formulations were successful. However, the results of the tablet hardness test have not met existing standards. The danger is the lack of PVP (Polyvinylpyrrolidone) excipients in the granules which cause the tablets to become brittle. To improve the formulation, the addition of the moisturizing agent can be done.